Distributed control monitoring system using Controller Area Network - Muhammad Amin, Ahmad Fairuz; Aris, Ishak
Network-based systems are widely used in many application areas such as intelligent systems and distributed systems. To design distributed systems, distributed information processing and intelligent terminals are required. This system can be integrated efficiently into the present automation management network system. This paper presents the development of distributed network control system based on Controller Area Network (CAN). The system includes three micro controller based boards with PIC18F458 with Analog-to-Digital (ADC) interface for analog measurement. The first board use a ADC input sensor for revolution per minute (RPM) calculation of motor, while the second board uses to capture temperature and the third board which connects to PC for Graphical User Interface (GUI) display for monitoring system. The three boards communicate via the existing data communications network. These micro controller based hardware devices are driven by programs written in the C programming language, while LabVIEW provides the user-control interface. This paper will present the methodology, design approach and results of the online monitoring system.